PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN INOVASI SDM TERHADAP KINERJA APARAT PEMERINTAH: KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI (STUDI PADA PEMERINTAH TINGKAT PROVINSI RIAU) - Dwi Mardaniati; Yesi Mutia Basri; M. Rasuli (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
This research aims to analyze the effect of budgeting participation and humanresources innovation towards the performance of government officials withorganization commitment and organization culture as moderation variable ingovernment Riau province level. The technique of selecting samples was by usingpurposive random sampling which obtained 115 civil servants as samples. Theresearcher used multiple linear regression technique and moderation regressionmodel/modereted regression analysis (MRA). The research results show that: 1)budgeting participation has effect towards the performance of government officials,2) human resources innovation has effect towards the performance of governmentofficials, 3) commitment moderates the correlational effect between budgetingparticipation and the performance of government officials, 4) organizational culturemoderates the correlational effect between budgeting participation and theperformance of government officials, 5) commitment moderates the correlationaleffect of human resources innovation and the performance of government officials,6) organizational culture moderates the correlational effect of human resourcesinnovation and the performance of government officials.